Weather the storms? Hurricanes, technology and oil production - Johan Brannlund; Geoffrey Dunbar; Reinhard Ellwanger; Matthew Krutkiewicz (Bank of Canada, 2022)
Do technological improvements mitigate the potential damages from extreme weather events? We address this question using oil production and hurricane data from the Gulf of Mexico. We show that hurricane activity lowers well production and that stronger storms have larger impacts that persist for months after impact. Hurricanes also significantly increase the probability that oil assets are stranded, particularly when the hurricanes pass within 50km of an oil rig's location. Regulations enacted in 1980 that required improved construction standards for rigs in the Gulf only modestly mitigated the short-run production losses caused by hurricanes. The 1980 regulatory reforms also modestly decreased the probability that leases permanently exited production.
Keywords: C22; C23; Q40; Q48; Q54; 330; Business fluctuations and cycles; Climate change; Potential output